Positive and negative ion emission from microdroplets by MeV energy ions. (July 2015) - Majima, T; Kitajima, K; Oonishi, Y; Ueda, H; Tsuchida, H; Itoh, A
Synopsis: We have developed a new experimental setup that allowed us to study collision interactions between fast ion beams and liquid droplets under a vacuum condition. Droplets of water and ethanol are irradiated with 0.4-1.5 MeV H + and 2.0 MeV C 2+ ions. The droplet diameter is estimated from energy loss measurements of projectile ions penetrating through droplets. Time-of-flight mass spectra of positive and negative secondary ions exhibit a series of cluster ions generated via protonation and deprotonation.